Fatigue and recovery after high-intensity exercise Part I: Neuromuscular fatigue - Lattier, G.; Millet, G. Y.; Martin, A.; Martin, V. (International Journal of Sports Medicine, 2004)
The contribution of central and peripheral factors to muscle fatigue were quantified following a high-intensity uphill running exercise. Eight male volunteers performed an intermittent exercise at 120 % of maximal aerobic speed on a treadmill with an 18 % grade. Electrically evoked and voluntary contractions of the knee extensors and EMG of the two vastii were analyzed before and immediately after the high-intensity exercise. Isometric maximal voluntary contraction decreased slightly (- 7 +/- 8 %; p < 0.05) after exercise but no changes were found in the level of maximal activation or in the torque produced by a 80 Hz maximal stimulation applied to the femoral nerve. Following exercise, the single twitch was characterized by lower peak torque, maximal rate of force development, and relaxation (- 28 +/- 11 %, - 25 +/- 12 %, - 31 +/- 15 % respectively, p < 0.001), and higher surface of the M-wave for both vastii. The ratio between the torques evoked by 20 Hz and 80 Hz stimulation declined significantly (- 22 +/- 10 %, p < 0.01) after exercise. These findings indicate that muscle fatigue after high-intensity running exercise is due to significant alteration in excitation-contraction coupling and that this type of exercise does not induce significant central fatigue or changes at the crossbridge level.